2020
DOI: 10.3389/fcimb.2020.541178
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Gut Microbiome Composition and Lipid Metabolic Profile in Radiation Enteritis

Abstract: Radiation enteritis (RE) is a common complication in cancer patients receiving radiotherapy. Although studies have shown the changes of this disease at clinical, pathological and other levels, the dynamic characteristics of local microbiome and metabolomics are hitherto unknown. We aimed to examine the multi-omics features of the gut microecosystem, determining the functional correlation between microbiome and lipid metabolites during RE activity. By delivering single high-dose irradiation, a RE mouse model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 51 publications
(54 reference statements)
5
62
0
Order By: Relevance
“…The applied 16S rRNA gene amplicon sequencing methods does, however, not make it possible to investigate this finding at a deeper taxonomic resolution. We observed that HFD mice have increased Dubosiella , which has been previously described in dysbiosis conditions such as GDM and obesity ( Bai et al, 2019 ; Li et al, 2020 ; Sheng et al, 2020 ; Qiu and Macchietto, 2021 ; Yi et al, 2021 ). Positive correlations of Dubosiella with FBG, FINS, and TC demonstrated that these bacteria may promote the glycolipid metabolism disorders, which could be reversed by ITF treatment.…”
Section: Discussionsupporting
confidence: 69%
“…The applied 16S rRNA gene amplicon sequencing methods does, however, not make it possible to investigate this finding at a deeper taxonomic resolution. We observed that HFD mice have increased Dubosiella , which has been previously described in dysbiosis conditions such as GDM and obesity ( Bai et al, 2019 ; Li et al, 2020 ; Sheng et al, 2020 ; Qiu and Macchietto, 2021 ; Yi et al, 2021 ). Positive correlations of Dubosiella with FBG, FINS, and TC demonstrated that these bacteria may promote the glycolipid metabolism disorders, which could be reversed by ITF treatment.…”
Section: Discussionsupporting
confidence: 69%
“…Walking spurred an enrichment on some intestinal bacteria, such as Akkermansia , Bacteroides , Dubosiella , and Lactobacillus . Bacteroides shows an enrichment at the early stage after irradiation, implying that the bacteria might be a driver for radiation toxicity ( Wang et al, 2019 ; Li et al, 2020b ). Yet the effect of Dubosiella on enteritis is still controversial ( Sheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been found that severe postirradiation enteropathy is associated with low mucosal bacterial diversity ( Ferreira et al, 2019 ). In rodent studies, specific findings of microbiota changes in postirradiation fecal samples include increased abundance of the phylum Proteobacteria and family Lactobacillaceae and decreased abundance of families Lachnospiraceae , Ruminococcaceae , and Clostridiaceae , with some changes observed out to 10 months ( Lam et al, 2012 ; Goudarzi et al, 2016 ; Zhao et al, 2019 ; Li et al, 2020 ). In humans, one prospective study of nine gynecologic cancer patients found that Firmicutes and Fusobacterium phyla were significantly decreased in fecal samples pre- versus post-pelvic irradiation ( Nam et al, 2013 ).…”
Section: The Effects Of Radiation On the Microbiomementioning
confidence: 99%